Opportunities and challenges in school-based sex and sexual health education in Nepal - Acharya, DR; Van Teijlingen, ER; Simkhada, P (Kathmandu University Medical Journal, 2010)
This article identifies and addresses opportunities for and challenges to current school-based sex and sexual health education in Nepal. Key literature searches were conducted of electronic databases and relevant web-sites, furthermore personal contact with experts and the hand searching of key journals was included. The review of this literature generated the following challenges: Limitations to teaching including lack of life skill-based and human right-based approach, inappropriate teaching aid and reliance on conventional methods, existing policy and practice, parental/community support, and lack of research into and evaluation of sex education. Diverse methodology in teaching, implementation of peer education programme, partnership with parents, involvement of external agencies and health professionals, capacity building of teachers, access to support and service organisation, and research and evaluation in sex education have been suggested for improving the current practice of sex and sexual health education in Nepalese schools. Key words: Sex education; education; school; adolescence; Nepal DOI: 10.3126/kumj.v7i4.2773 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 445-453